Examining the Relationship Between the Aspects of School Working Conditions and Teachers’ Intent to Stay as Mediated by Job Satisfaction - Petros Woldu Fessehatsion; Pai Peng (European Scientific Journal, ESJ, 2022)
This study sought to examine the relationship among the aspects of school condition, job satisfaction, and intent to stay with a sample size of 833 teachers working at elementary, middle, and secondary schools in the central administration of Eritrea. Survey data were analyzed using a structural equation model (SEM). Our results showed that teachers were more likely to stay in their profession when they experienced supportive school leadership, effective professional development, and more access to school resources. Besides, the study revealed that early career teachers are more likely to leave than their mid-career, and veteran counterparts. Moreover, the findings demonstrated that overall job satisfaction partially mediates the relationship between intent to stay and (a) leadership support, (b) school resources, (c) professional development, and (d) students’ discipline. The practical implication of the findings suggested that measures targeting the improvement of the school environment should also aim to enhance overall job satisfaction to retain teachers in their profession.